Just politics : human rights and the foreign policy of great powers - Walldorf, C. William, Jr., 1967- (Ithaca : Cornell University Press, 2008)
Many foreign policy analysts assume that elite policymakers in liberal democracies consistently ignore humanitarian norms when these norms interfere with commercial and strategic interests. Today's endorsement by Western governments of repressive regimes in countries from Kazakhstan to Pakistan and Saudi Arabia in the name of fighting terror only reinforces this opinion. In Just Politics, C. William Walldorf Jr. challenges this conventional wisdom, arguing that human rights concerns have often led democratic great powers to sever vital strategic partnerships even when it has not been in their interest to do so. Walldorf sets out his case in detailed studies of British alliance relationships with the Ottoman Empire and Portugal in the nineteenth century and of U.S. partnerships with numerous countries-ranging from South Africa, Turkey, Greece and El Salvador to Nicaragua, Chile, and Argentina-during the Cold War. He finds that illiberal behavior by partner states, varying degrees of pressure by nonstate actors, and legislative activism account for the decisions by democracies to terminate strategic partnerships for human rights reasons. To demonstrate the central influence of humanitarian considerations and domestic politics in the most vital of strategic moments of great-power foreign policy, Walldorf argues that Western governments can and must integrate human rights into their foreign policies. Failure to take humanitarian concerns into account, he contends, will only damage their long-term strategic objectives.
Introduction : human rights and foreign policy -- Humanitarianism and commitment termination -- Suffering Christians in British-Ottoman relations -- Torture and summary execution in U.S.-Latin American relations -- Apartheid in U.S.-South African relations -- Human rights and vital security -- The implications of enforced humanitarian norms.
Includes bibliographical references (pages 185-219) and index.
Keywords: 1837-1989; Human rights; International relations; Alliances; Droits de l'homme (Droit international); Relations internationales; international relations; Political science -- Human Rights; Political science -- Political Freedom & Security -- Civil Rights; Political science -- Political Freedom & Security -- Human Rights; Diplomatic relations; Alliances; Human rights; International relations; United States -- Foreign relations -- 1945-1989.; Great Britain -- Foreign relations -- 1837-1901.; Etats-Unis -- Relations exterieures -- 1945-1989.; Grande-Bretagne -- Relations exterieures -- 1837-1901.; Great Britain; United States